Design and technical validation of a wearable biofeedback system for robotic gait rehabilitation - Pinheiro, Cristiana (2020)
Gait disabilities affect the human quality of life. Current directions for time-effective robotic gait rehabilitation require the inclusion of biofeedback systems (BSs) as a complementary robotic tool for efficient motor relearning. This work aims to present the user-centered design and validation of a wearable BS to foster users' active participation and enable therapists' effective participation during robotic gait rehabilitation driven by active orthoses. The multimodal BS comprises a development board to manage the activation of the stimuli (vibrotactile through the vibrotactile waist and shank bands, sonorous via single earphone, and visual using RGB LED) according to data tracked by orthosis embedded sensors. The BS's versatility allows its functioning as a modular and stand-alone system or integrated into the orthotic system. The system's operability was validated with four healthy subjects walking on a treadmill with the orthotic system and BS at 1 km/h. The results showed an operable system with good usability during robotic gait rehabilitation. This wearable BS has the potential to boost symmetric gait recovery and to effectively augment the user's active participation during robotic gait therapy; thus, contributing to accelerating the user's motor recovery.